2022
DOI: 10.1186/s43141-022-00448-8
|View full text |Cite
|
Sign up to set email alerts
|

Application of 16S rRNA virtual RFLP for the discrimination of some closely taxonomic-related lactobacilli species

Abstract: Background Several species in Lactobacillaceae family were recognized as potential probiotic bacteria. In this group of lactic acid bacteria, species are taxonomically closed and usually share similar 16S rRNA gene, thus, instead of so their identification and discrimination are too difficult. Method In the present study, virtual restriction fragment length polymorphism (RFLP) is instead of was used as a tool to discriminate between the closely rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…casei DSM 20011 T ( Supplementary Figure S1A ). On the other hand, Laref and Belkheir (2022) reported that seven endonucleases were required to separate LCG species. To overcome this caveat, we developed a fast PCR assay targeting a Lcb.…”
Section: Resultsmentioning
confidence: 99%
“…casei DSM 20011 T ( Supplementary Figure S1A ). On the other hand, Laref and Belkheir (2022) reported that seven endonucleases were required to separate LCG species. To overcome this caveat, we developed a fast PCR assay targeting a Lcb.…”
Section: Resultsmentioning
confidence: 99%
“…The genetic diversity of these culturable endophytic bacteria was investigated by molecular methods, i.e., 16S rDNA-RFLP analysis followed by housekeeping gene sequence analysis. 16S rDNA-RFLP can help efficiently discriminate closed species and has been widely used in the genetic diversity analysis of prokaryotes (Chen et al, 2018 ; Laref and Belkheir, 2022 ). According to 16S rDNA-RFLP analysis, 114 endophytic bacteria were clustered into 32 groups, which showed great genetic diversity.…”
Section: Discussionmentioning
confidence: 99%